PENGARUH EDUKASI GIZI BERBASIS PERMAINAN BALOK UNO TERHADAP PENINGKATAN PENGETAHUAN DAN SIKAP GIZI ANAK SEKOLAH DASAR MI DDI UJUNG LARE PAREPARE: The Effect of Uno Block Game-Based Nutrition Education on Increasing Knowledge and Nutritional Attitudes of Elementary School Children MI DDI Ujung lare Parepare - Mustamin, Mustamin; Sunarto, Sunarto; Rauf, Suriani; Sri Lestari, Retno; Syamsiar (Media Gizi Pangan, 2024)
Nutrition is one of the important components of the health sector that plays a crucial role in public health. Good nutrition is the foundation for individuals to reach their full potential. This study aimed to determine and analyze the effect of nutrition education based on Uno block game on improving knowledge and attitude of primary school children before and after receiving nutrition education. The study design was a quasi-experiment with a pre-test post-test design conducted at MI DDI Ujung Lare Parepare. The sample size was 44 participants. Knowledge and attitude towards nutrition were collected through questionnaires, and statistical analysis was performed using the Wilcoxon test. The results showed that the age of the students was mostly 10 years old (68.2%), the majority of students were in grade 4 (52.3%), and male students comprised 59.1% of the sample. The majority of fathers were entrepreneurs (27.3%), while the majority of mothers were civil servants/military/police officers (45.5%). The level of knowledge of students before and after receiving nutrition education was 63.6%. The level of attitude towards nutrition of students before and after receiving education was 95.5% and 100%, respectively. The statistical analysis showed that there was a significant difference in knowledge before and after receiving nutrition education (p=0.000). However, there was no significant difference in attitude before and after education (p=0.157). In conclusion, there was a significant improvement in nutrition knowledge after receiving education based on the Uno block game. However, there was no significant improvement in attitude towards nutrition. Further research is recommended to develop this study based on the Uno block game.